2016
DOI: 10.1002/2015jc011265
|View full text |Cite
|
Sign up to set email alerts
|

Sea level anomaly on the Patagonian continental shelf: Trends, annual patterns and geostrophic flows

Abstract: We study the annual patterns and linear trend of satellite sea level anomaly (SLA) over the southwest South Atlantic continental shelf (SWACS) between 54ºS and 36ºS. Results show that south of 42°S the thermal steric effect explains nearly 100% of the annual amplitude of the SLA, while north of 42°S it explains less than 60%. This difference is due to the halosteric contribution. The annual wind variability plays a minor role over the whole continental shelf. The temporal linear trend in SLA ranges between 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…Numerical simulations suggest that the inner and middle shelf circulation is primarily driven by the alongshore component of the wind stress (Palma et al, ). Seasonal geostrophic currents derived from satellite altimetry data south of 36°S present a mean flow to the north all year‐round, with weak seasonal variability, and a slight wind‐driven increase in autumn‐winter (April–July; Strub et al, ; Ruiz‐Etcheverry et al, ). Short‐term observations (Lanfredi, ; Lanfredi & Capurro, ) along with numerical models (Combes & Matano, ; Forbes & Garraffo, ; Glorioso & Flather, ) also show a mean flow in the ACS toward the NNE and indicate that tidal currents north of 40°S are relatively weak.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations suggest that the inner and middle shelf circulation is primarily driven by the alongshore component of the wind stress (Palma et al, ). Seasonal geostrophic currents derived from satellite altimetry data south of 36°S present a mean flow to the north all year‐round, with weak seasonal variability, and a slight wind‐driven increase in autumn‐winter (April–July; Strub et al, ; Ruiz‐Etcheverry et al, ). Short‐term observations (Lanfredi, ; Lanfredi & Capurro, ) along with numerical models (Combes & Matano, ; Forbes & Garraffo, ; Glorioso & Flather, ) also show a mean flow in the ACS toward the NNE and indicate that tidal currents north of 40°S are relatively weak.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the MDT shows a consistent pattern over the continental shelves comparing with in situ measurements and the geostrophic velocities from MADT have errors in the order of 12 cm/s over the broad Gulf Stream Current Area (20°N–60°N, 275°E–340°E) [ Rio et al ., ]. Despite the uncertainty of the SLA over the shallow waters, this data set is valuable to describe physical processes on the continental shelf [e.g., Ruiz et al ., ; Gawarkiewicz et al ., ; Strub et al ., ; Ruiz Etcheverry et al ., ]. Moreover, if taken monthly mean, the error of the derived velocities will be further reduced (e.g., 4∼6 cm/s given a SLA decorrelation scale of 4 days) [ Ponte , ].…”
Section: Methodsmentioning
confidence: 99%
“…southwestern Atlantic (SWA): BC, Brazilian warm current; MC, Malvinas/Falkland cold current (branch of the ACC); PC, Patagonian coastal cold current (Subantarctic shelf waters); ACC, Antarctic Circumpolar Current; BMCZ, Brazil-Malvinas Confluence Zone; SAF, Subantarctic Front; PF, Polar Front; ACC, Antarctic Circumpolar Current; SSW: southern westerly winds; PE: Polar easterlies; arrows indicate direction of winds (darker arrows correspond to maximum wind speeds). In the Southeastern Pacific: CHC, Cabo de Hornos Current; HC, Humboldt Current; WWW, West Wind Drift = Antarctic Convergence Current (ACC); information taken from Acha et al, 2004;Bianchi et al, 2005;Palma et al, 2008, Piola andFalabella, 2009;Glembocki et al, 2015;Olguín-Salinas et al, 2015;Ruiz-Etcheverry et al, 2016;Kahl et al, 2017;Piola et al, 2018;Combes and Matano, 2018;Franco et al, 2018; other references therein and in A.6). Biogeographical regions: A, Argentinean malacological province; M, Magellanean malacological province.…”
Section: Modern Patagonian Littoral Settingmentioning
confidence: 99%
“…Apart from that, higher δ 18 O values can be linked to higher salinity and/or to enhanced upwelling of cold nutrient-rich waters at coastal fronts (Bianchi et al, 2005). For instance, the modern δ 18 O -and δ 13 C -maxima occur in the northern Golfo San Matías (NSAO), where the influence of warm waters together with a reverse circulation and a longer residence time for shallow waters, are responsible for enhanced evaporation and higher salinity (Piola and Rivas, 1997;Guerrero and Piola, 1997;Rivas and Pisoni, 2010;Ruiz-Etcheverry et al, 2016), leading to higher δ 18 O values (Figs. 3, 4, 9).…”
Section: Oxygen-isotope Variationmentioning
confidence: 99%